Facile heterocyclic synthesis and antimicrobial activity of polysubstituted and condensed pyrazolopyranopyrimidine and pyrazolopyranotriazine derivatives - Hafez Hend N.; Alshammari Abdulrahman G.; El-Gazzar Abdel-Rhman B. A. (Acta Pharmaceutica)
Reaction of 6-amino-3-methyl-4-(substituted phenyl)-1,4- dihydropyrano[2,3-c]pyrazole-5-carbonitrile (1) with triethylorthoformate followed by treatment with hydrazine hydrate, formic acid, acetic acid, phenylisocyanate, ammonium thiocyanate and formamide afforded the corresponding pyranopyrimidine derivatives 2-6. Cyclocondensation of 1 with cyclohexanone afforded pyrazolopyranoquinoline 7. One-pot process of diazotation and de-diazochlorination of 1 afforded pyrazolopyranotriazine derivative 8, which upon treatment with secondary amines afforded 9 and 10a- c. Condensation of 2 with aromatic aldehyde gave the corresponding Schiff bases 11a,b, the oxidative cyclization of the hydrazone with appropriate oxidant afforded 11-(4- fluorophenyl))- 2-(4-substituted phenyl)-10-methyl-8,11-dihydropyrazolo-[ 4’,3’:5,6]pyrano[3,2-e][1,2,4]triazolo[1,5-c]pyrimidines (12a,b). Structures of the synthesized compounds were confirmed by spectral data and elemental analysis. All synthesized compounds were evaluated for antibacterial and antifungal activities compared to norfloxacin and fluconazole as standard drugs. Compounds 9, 10c, 12a and 15 were found to be the most potent antibacterial agents, with activity equal to that of norfloxacin. On the other hand, compound 5 exhibited higher antifungal activity compared to fluconazole.